Eurobachelor in Chemistry - Bulgaria's Odds? [In Bulgarian] - B.V. Toshev (University of Sofia, 2008)
The Bachelor education in chemistry is presented in the Universities of Sofia, Plovdiv, Shumen and Blagoevgrad. The chemistry education in the University of Sofia has a long tradition. The paper examines the rules and criteria for obtaining the Eurobachelor label, developed by the European Chemistry Thematic Network (ECTN). The comparative analysis of the existing program with these European criteria shows that the eventual application of the University of Sofia for that label seems to be untimely at the present moment.